Acquiring limited liability company in Latvia - Berga, Signe (Riga Graduate School of Law, 2021)
Analyzing previous research on decision making of cross-border merger and acquisition, which allowed to identify country-specific characteristics that has influence particularly on the choice of host country of targeted company, the current attractiveness of Latvia to foreign direct investment was clarified and it appears, that perception of Latvia in international reports is above average, however, stakeholders of publicly listed companies perceive acquisition of equity to be riskier compared to purchase of separate assets. Moreover, when Latvia is chosen as a host country for potential business acquisition, each deal structure has its advantages and disadvantages, but none has significant influence on the cost of the transaction from the perspective of value added tax, if all the precautions are taken into consideration.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Research Subject Categories::LAW/JURISPRUDENCE::Private law::Commercial and company law; Latvia